MAKNA ASOSIATIF DALAM KITAB MAZMUR - KASOPA, JEANETA KRISYA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACTS Â This research entitled â€œThe Associative Meaning in Book of Psalmâ€. The problems of this research focus on the five types of Associative Meaning and their descriptions in the Book ofÂ Psalm. The aims of the research are to identify, classify, and to analyze the verses in the Book of Psalms using Semantics approach. Â This research uses descriptive method supported by Leechâ€™s theory. In collecting data, the writer focused on reading the words, phrases, or sentences in every verse from chapter 1-50. The result of this research showed that there areÂ connotative meaning, social meaning, affective meaning, reflective meaning, and collocative meaning in the Book of Psalm. Â Keywords: Associative Meaning, Book of Psalm, Descriptive Analysis